Complicit in Their Own Demise?. Issue 4 (22nd April 2014) - Parks, Gregory S.; Ray, Rashawn; Jones, Shayne E.; Hughey, Matthew W.
<x xml:space="preserve">Abstract</x> Violent hazing has been a longstanding issue within African American, collegiate fraternities and sororities, otherwise known as black Greek‐letter organizations (BGLOs). This article investigates how and what hazing victims know about their hazing experiences. Additionally, the article examines how victims' knowledge of hazing may hold serious implications for tort defense doctrines like assumption of risk and comparative fault. Specifically, the authors conduct two studies—one quantitative and the other qualitative—to find that not only are BGLO pledges aware that their pledge experiences are likely to involve mental and physical hazing, but that they believe such experiences will likely continue throughout the entirety of their induction process. Moreover, appreciation for hazing experiences is often captured in the fraternal chants, greetings, and songs they learn or create, which together reflects some understanding of danger and risk. The authors contend that these elements of black "Greek" hazing culture may serve as evidence of assumption of risk or comparative fault.